Sustainability in Hospitality: An Implementation of Green Practices in Housekeeping at Radisson Blu Bali Uluwatu - Winanti, Ni Nyoman Marsya; Suastini, Ni Made; Dianasari, Dewa Ayu Made Lily (Journal of Hospitality Accommodation Management (JHAM), 2025)
The implementation of green practices in housekeeping operations is a vital effort to support environmental sustainability in the hospitality industry. This study aims to investigate the application of green practices in the housekeeping operations at Radisson Blu Bali Uluwatu, identify the obstacles faced, and analyze the implications for the environment and surrounding communities. This research uses a descriptive qualitative method with data collection techniques including observations, in-depth interviews with hotel management, and validation through expert interviews. The results show that Radisson Blu Bali Uluwatu has implemented several green practice programs such as linen and towel reuse, the use of environmentally friendly products, waste separation, and energy efficiency. However, several challenges remain, including variations in staff understanding, limited recycling infrastructure, and low guest participation. The implementation of green practices has a positive impact by reducing resource consumption, improving waste management, empowering local SMEs, and strengthening Bali's image as a sustainable tourism destination. This study highlights that the success of green practice initiatives requires continuous support from both internal hotel operations and the surrounding community.